2008
DOI: 10.2967/jnumed.108.051235
|View full text |Cite
|
Sign up to set email alerts
|

Tariquidar-Induced P-Glycoprotein Inhibition at the Rat Blood–Brain Barrier Studied with (R)-11C-Verapamil and PET

Abstract: The multidrug efflux transporter P-glycoprotein (P-gp) is expressed in high concentrations at the blood-brain barrier (BBB) and is believed to be implicated in resistance to central nervous system drugs. We used small-animal PET and (R)-11 Cverapamil together with tariquidar, a new-generation P-gp modulator, to study the functional activity of P-gp at the BBB of rats. To enable a comparison with human PET data, we performed kinetic modeling to estimate the rate constants of radiotracer transport across the rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
96
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(107 citation statements)
references
References 27 publications
9
96
2
Order By: Relevance
“…The K p obtained for individual doses of elacridar and tariquidar are low as a result of the low concentrations of either P-gp modulator in the brain. These results contrast with prior studies that showed that the levels of tariquidar and elacridar were much higher in the brain than in the plasma (Bankstahl et al, 2008;Kuntner et al, 2010), but those experiments used between 3.0-and 15-fold higher doses of P-gp modulators compared with the current study. These differences were properly explained before (Kawamura et al, 2011;Sane et al, 2013), where murine models revealed that at higher doses of elacridar, a higher distribution of the P-gp modulator was attained in the brain.…”
Section: Discussioncontrasting
confidence: 56%
“…The K p obtained for individual doses of elacridar and tariquidar are low as a result of the low concentrations of either P-gp modulator in the brain. These results contrast with prior studies that showed that the levels of tariquidar and elacridar were much higher in the brain than in the plasma (Bankstahl et al, 2008;Kuntner et al, 2010), but those experiments used between 3.0-and 15-fold higher doses of P-gp modulators compared with the current study. These differences were properly explained before (Kawamura et al, 2011;Sane et al, 2013), where murine models revealed that at higher doses of elacridar, a higher distribution of the P-gp modulator was attained in the brain.…”
Section: Discussioncontrasting
confidence: 56%
“…In contrast, effects of tariquidar on Q out and V br were similar in all brain regions studied in the present study (Table 4). Verapamil, however, is a much stronger P-gp substrate than flumazenil, showing a more than 1,000% increase in brain concentrations after P-gp inhibition with a 15 mgÁkg 21 dose of tariquidar (29,36), and it is possible that regional differences between flumazenil brain concentrations at baseline and after P-gp inhibition are too small to be detected. The present study also showed that the effects of tariquidar were similar for kainate-treated animals and controls ( Table 2).…”
Section: Discussionmentioning
confidence: 94%
“…may affect both carriers. The effective TAR dose described in the literature that is necessary to achieve the in vivo P-gp inhibition effect is usually 15 mg/kg (40)(41)(42), which was the dose used in the present study. Unfortunately, a prototypical P-gp inhibitor is currently not available and the dosing regimen used in this work does not allow us to conclude whether the observed efflux inhibition is due to P-gp only or whether BCRP transporters are also involved in LEV's prostate penetration.…”
Section: Discussionmentioning
confidence: 99%